The low evolutionary rate of human T-cell lymphotropic virus type-1 confirmed by analysis of vertical transmission chains - Van Dooren, Sonia (2004)
Rega Institute for Medical Research. Katholieke Universiteit Leuven. Leuven, Belgium.